Analysis of Radiation Heat Transfer of a Micropolar Fluid with Variable Properties over a Stretching Sheet in the Presence of Magnetic Field - Reza Keimanesh; Cyrus Aghanajafi (Journal of Heat and Mass Transfer Research, 2016)
The present study deals with the analysis of the effects of radiative heat transfer of micropolar fluid flow over a porous and stretching sheet in the presence of magnetic field. The dynamic viscosity and thermal conductivity coefficient have formulated by temperature-dependent relations to obtain more exact results. The flow is supposed two-dimensional, incompressible, steady and laminar and the applied magnetic field is assumed uniform. On the other hand, the velocity of the isothermal stretching sheet varies linearly with the distance from a fixed point on the sheet. The governing equations have extracted using the theory of micropolar fluid and the boundary layer approximation. Then they have been solved by similarity solution relationships, shooting method and fourth-order Runge-Kutta method. The results express that the presence and increase of variable thermal conductivity parameter, magnetism, radiation and variable viscosity parameter cause to decrease of heat transfer from the sheet, while increase of material parameter, Prandtl number and suction parameter increase the rate of heat transfer from the sheet. Also the values of dimensionless velocity are enhanced by increase of variable thermal conductivity parameter, material parameter and radiation parameter. On the other hand, the values of dimensionless angular velocity are completely influenced by the values of the velocity gradient.